National Cancer Database Report of Lymphadenectomy Trends in Endometrial Cancer. Issue 7 (September 2017) - Cripe, James; Handorf, Elizabeth; Brown, Jennifer; Jain, Angela; Rubin, Stephen; Mantia-Smaldone, Gina
Abstract : Objectives: Lymph node involvement has a significant impact on prognosis that may direct adjuvant therapy. The role of routine lymph node staging (LNS) is controversial given conflicting results in multiple studies. Our aims are to describe treatment patterns of LNS, identify factors impacting LNS, and quantify the contemporary trends. Methods/Materials: The National Cancer Data Base was queried for patients undergoing hysterectomy for endometrioid and serous uterine carcinomas from 2003 to 2012. For endometrioid tumors, LNS was considered indicated if at least 1 of 4 criteria was met. Multivariate logistic regression and Cox proportional hazards model were used. Results: A total of 161, 683 patients were identified who received hysterectomy for 155, 893 (96.4%) endometrioid and 5790 (3.6%) serous carcinomas. Receipt of LNS was significantly associated with greater than 50% myometrial invasion (odds ratio [OR], 1.63; 95% confidence interval [CI], 1.55–1.73), grades 3 to 4 (OR, 3.03; 95% CI, 2.83–3.25), and tumor size greater than 2 cm (OR, 1.17; 95% CI, 1.28–1.26). Of the 97, 152 patients with endometrioid carcinoma who met criteria for comprehensive staging, 73, 268 (75.4%) underwent LNS. Patients with endometrioid carcinoma meeting criteria for LNS were less likely to receive LNS if they were of African American race (OR, 0.92; 95% CI, 0.86–0.98), had Medicaid insurance status (OR, 0.75; 95% CI, 0.69–0.81), had Medicare insurance (OR, 0.82; 95% CI, 0.79–0.86), or received care at a community program (OR, 0.39; 95% CI, 0.33–0.46). Conclusions: Nationally, most patients with greater than 50% myometrial invasion, grades 3 to 4, and/or tumor size greater than 2 cm receive LNS, but this was significantly impacted by insurance status, demographic characteristics, and facility location/type.